PENGARUH UPAH, BAHAN BAKU, DAN LAMA USAHA TERHADAP PRODUKSI INDUSTRI PATUNG KAYU DI KECAMATAN SUKAWATI KABUPATEN GIANYAR - Kristina, Ni Made; Arka, Sudarsana (E-Jurnal Ekonomi Pembangunan Universitas Udayana, 2021)
The sculpture handicraft industry in Sukawati Subdistrict received attention from both domestic and foreign tourists, but Sukawati sub-district has not yet maximized the amount of wood sculpture production. There are various factors that can influence the production of the wooden sculpture industry. The purpose of this study was to analyze the effect of wages, raw materials and length of business simultaneously affect the production of wood sculpture industry in Gianyar Regency and analyze the effect of wages, raw materials and length of business partially influence the production of wood sculpture industry in Gianyar Regency. The population of this research is all wood sculpture business in Sukawati District, Gianyar Regency. The sample used was 100 units of wood sculpture craft business in Sukawati District, Gianyar Regency. The analysis technique used in this study is multiple linear regression analysis. The results of the analysis of this study indicate that wages, raw materials and business length simultaneously have a significant effect on the production of the Wood Sculpture Industry in Sukawati District. Wages and raw materials partially have a positive effect on the production of the Wood sculpture industry in Sukawati District, while the length of business has no effect on the production of the Wood sculpture industry in Sukawati District. Keywords: Work Experience, Working Hours, Production, Profits.